2020
DOI: 10.22531/muglajsci.643554
|View full text |Cite
|
Sign up to set email alerts
|

An Early Prediction and Diagnosis of Sepsis in Intensive Care Units: an Unsupervi̇sed Machine Learning Model

Abstract: Sepsis infection, which is one of the most important causes of death in intensive care units, is seen as a severe global health crisis. If an early diagnosis of sepsis infection cannot be made, and treatment is not started rapidly, septic shock may result in multiple organ failure and death is almost inevitable. Therefore, it is vital to establish an early diagnosis and start the treatment at once. This study aims to accomplish a new model of unsupervised machine learning using lactate and Ph laboratory test v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Support Vector Machine (SVM), Logistic Regression (LR), and XGBoost classification algorithms were employed in the study by Ergul Aydn & Kamişli Ozturk, [8] one of the comparable studies in this field, to assess whether the patients' stays in critical care were longer than 3 days. The study found that, similarly to earlier prediction articles, the XGBoost classifier outperformed Support Vector Machine (SVM) and Logistic Regression (LR) [9,10,11,12]. Poucke's study was to compare the predictive performance of Decision Tree, Naïve Bayes, Logistic and Regression methods, and ensemble learning methods (Random Forest, Boosting, and Bagging) when assessing the predictive power of laboratory tests for hospital mortality in patients admitted to the intensive care unit.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Support Vector Machine (SVM), Logistic Regression (LR), and XGBoost classification algorithms were employed in the study by Ergul Aydn & Kamişli Ozturk, [8] one of the comparable studies in this field, to assess whether the patients' stays in critical care were longer than 3 days. The study found that, similarly to earlier prediction articles, the XGBoost classifier outperformed Support Vector Machine (SVM) and Logistic Regression (LR) [9,10,11,12]. Poucke's study was to compare the predictive performance of Decision Tree, Naïve Bayes, Logistic and Regression methods, and ensemble learning methods (Random Forest, Boosting, and Bagging) when assessing the predictive power of laboratory tests for hospital mortality in patients admitted to the intensive care unit.…”
Section: Introductionmentioning
confidence: 82%
“…For specialists doing various studies on intensive care research, from the creation of clinical decision support algorithms to a better comprehension of retrospective clinical investigations, the MIMIC-II and MIMIC-III databases are crucial sources of data. Despite advances in disease identification and treatment, the rate of mechanical ventilation, sepsis infection and mortality in intensive care units have been growing recently [12,29,32,33]. Globally, deaths in intensive care units are seen as a severe health concern.…”
Section: Li̇terature Revi̇ewmentioning
confidence: 99%
“…Prediction models based on machine learning have been successfully applied in the diagnosis and detection of many diseases in the field of health for the last few years [17]. These models have some advantages, such as rapid processing and generating results with minimum human intervention.…”
Section: -1-literature Surveymentioning
confidence: 99%